The public sector wage premium puzzle. (18th May 2019) - Wang, Yi; Zhou, Peng
This paper investigates the public sector wage premium in the UK over the first decade of the 21st century using both econometric and economic modelling methods. A comprehensive literature review is conducted to summarise the four popular types of methods adopted by the traditional microeconometric studies. Application of these methods results in an estimated public sector wage premium equal to 6.5%. Indirect inference is then introduced as a new method of testing and estimating a microfounded economic model. All four types of econometric methods can be used as auxiliary models to summarise the data features, based on which the distance between the actual data and the model-simulated data is assessed. The selection bias can also be tested in a straightforward way under indirect inference.